2020
DOI: 10.1111/resp.13964
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of CPAP outcome in hospitalized COVID‐19 patients

Abstract: https://youtu.be/9GADRnfBHSc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Initial reports of NIV use in Covid 19 showed that CPAP trial succeed in 40% when used in those requiring >15 L/min of O2 by nonrebreathing mask with baseline SpO 2 /FiO 2 (SFR) of >110, RR > 30/min and NLR > 8. Repeat SFR at 30-120 min improved in all patients but cut off of SFR 180 was the best predictor of success or failure of CPAP trial but patients who failed had high mortality (38%) [10]. Intubation rates and mortality in Covid 19 patients who received NIV was similar to the group which received HFNC.…”
Section: Niv In Covid-19 Pneumoniamentioning
confidence: 74%
“…Initial reports of NIV use in Covid 19 showed that CPAP trial succeed in 40% when used in those requiring >15 L/min of O2 by nonrebreathing mask with baseline SpO 2 /FiO 2 (SFR) of >110, RR > 30/min and NLR > 8. Repeat SFR at 30-120 min improved in all patients but cut off of SFR 180 was the best predictor of success or failure of CPAP trial but patients who failed had high mortality (38%) [10]. Intubation rates and mortality in Covid 19 patients who received NIV was similar to the group which received HFNC.…”
Section: Niv In Covid-19 Pneumoniamentioning
confidence: 74%
“…The components of the A-a gradient are measures of ventilation-perfusion (VQ) mismatch, diffusion abnormalities and changes in ventilation (Co2). In ARF due to SARS-COV-2, patients present with severe hypoxemic hypocapnoeic alkalosis where it has been speculated that the PaO2/FiO2 (PF) ratio is an underestimate of hypoxaemia unlike the A-a gradient, because the PaO2 values standardised to PaCO2 levels is not calculated (1,66*PaCO2-PaO2 – 66,4 mmHg) 12,23 . We show a higher correlation between the ROX index and the A-a gradient, as opposed to the PF ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The practical ease of measurement of the ROX, in contrast to arterial blood sampling makes it easy for repetitive measurements using existent observations. Previous investigators have suggested the use of the SF (SpO2/FiO2) ratio 12 which may be prone to inaccuracies of the oxygen dissociation curve with saturations < 92%. This limitation has been reported to be mitigated by the addition of the respiratory rate: the ROX index 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In clinical trials, this efficacy is around 65-70%: 66.6% with CPAP 22 ; 65.7% with HNFC 23 ; 70% with CPAP (HENIVOT) 24 . In other observational studies, an efficacy of NIRS in avoiding OTI-IMV of around 40% is described: 37% with CPAP 18 ; 40% with CPAP 25 .…”
Section: Introductionmentioning
confidence: 88%